World Health Organization AWaRe framework for antibiotic stewardship: Where are we now and where do we need to go? An expert viewpoint - Steward Mudenda; Victor Daka; Scott K. Matafwali (Cambridge University Press, 2023)
The AWaRe classification categorizes antibiotics and is a tool for antimicrobial stewardship. To combat antimicrobial resistance, prescribers must adhere to the AWaRe framework, which promotes the rational use of antibiotics. Therefore, increasing political will, dedicating resources, building capacity, and improving awareness and sensitization campaigns may promote adherence to the framework.